2017
DOI: 10.3168/jds.2016-11577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral calcium administration on the cure and reproductive performance of Holstein cows diagnosed with puerperal metritis

Abstract: Our objective was to evaluate the effect of oral calcium administration on clinical cure, survival, subsequent presentation of peripartal health disorders, and reproductive performance of Holstein cows diagnosed with puerperal metritis (PM) under certified organic management. A second objective was to evaluate the metabolic status at calving and at the time of PM diagnosis (d 0) in affected and matched healthy cows. Cows diagnosed with PM (n = 200) were assigned randomly to receive 1 of 2 treatments: (1) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
4
9
0
1
Order By: Relevance
“…The authors speculated that the observed low calcium values might also be an indicator of inadequate feed intake rather than metabolic disease when considering such a long risk period. This assumption is in agreement with Pinedo et al (2017), who suggested that hypocalcemia might be caused by insufficient feed intake before clinical signs of postpartum diseases. Using a matched pair comparison, Jawor et al (2012) detected greater milk yield (+6 kg/d) during wk 2, 3, and, 4 postpartum for cows suffering from subclinical hypocalcemia 0 to 24 h after calving (<1.8 mmol/L).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors speculated that the observed low calcium values might also be an indicator of inadequate feed intake rather than metabolic disease when considering such a long risk period. This assumption is in agreement with Pinedo et al (2017), who suggested that hypocalcemia might be caused by insufficient feed intake before clinical signs of postpartum diseases. Using a matched pair comparison, Jawor et al (2012) detected greater milk yield (+6 kg/d) during wk 2, 3, and, 4 postpartum for cows suffering from subclinical hypocalcemia 0 to 24 h after calving (<1.8 mmol/L).…”
Section: Discussionsupporting
confidence: 91%
“…Although these epidemiological studies showed an association and some evidence for a causal relationship between hypocalcemia and an increased risk for infectious diseases (Martinez et al, 2014), longer risk periods have to be evaluated with caution. It is also possible that reduced feed intake affects serum calcium levels before clinical signs of disease become apparent, as most recently shown by Pinedo et al (2017) for cows suffering from puerperal metritis. Considering a relatively long risk period of 1 wk might lead to an underestimation of the prevalence and an overestimation of the effect size caused by hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover,it is also probable that lower feed intake prior to clinical signs of disease can have an effect on serum calcium levels. These observations are in accordance with many investigators [27][28][29][30]. It has been shown that the alterations in Ca metabolism caused by lactation are more substantial than parturition as there is loss of blood Ca to milk [3].…”
Section: Discussionsupporting
confidence: 93%
“…Dystocia has been associated with poor mineral, energetic, and immune profiles, which are factors that also increase the risks of other disorders, such as RFM, PM, and culling in dairy cattle (Gröhn and Rajala-Schultz, 2000;Gilbert, 2016;Pinedo et al, 2017). In the present study, we observed that shorter time in the close-up groups was a risk factor for DYS.…”
Section: Discussionsupporting
confidence: 50%